2001
DOI: 10.1159/000052964
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Study of the Uterine Arteries and Ovarian Stroma in Patients with Polycystic Ovary Syndrome

Abstract: Doppler analysis of the uterine arteries and ovarian stroma was performed by transvaginal ultrasound in 24 patients with polycystic ovary syndrome (PCOS) and 22 ovulatory women. Vascularization of the ovarian stroma was more abundant in patients with PCOS than in control women, but no significant difference in the mean pulsatility index (PI) was observed between groups (1.14 ± 0.28 for the PCOS group and 1.05 ± 0.19 for the control group). The mean PI of the uterine arteries was significantly higher in the PCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 28 publications
2
14
1
1
Order By: Relevance
“…The results of our study and those of previous studies, which focused on uterine arterial blood flow resistance in the follicular phase (10–18), suggest that an elevated uterine arterial PI may be a cardiovascular risk factor. Furthermore, impaired uterine perfusion in the luteal phase may be closely associated with abnormalities in endometrium and failure of implantation.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The results of our study and those of previous studies, which focused on uterine arterial blood flow resistance in the follicular phase (10–18), suggest that an elevated uterine arterial PI may be a cardiovascular risk factor. Furthermore, impaired uterine perfusion in the luteal phase may be closely associated with abnormalities in endometrium and failure of implantation.…”
Section: Discussionsupporting
confidence: 79%
“…Previous reports showed that the androstenedione (10,11), dehydroepiandrosterone (16), or dehydroepiandrosterone sulfate level (18) is associated with an elevated uterine arterial PI. However, there is a report that no correlation was observed between the androstenedione or testosterone level and the uterine arterial PI (17). Testosterone is known to induce vasodilation or vasoconstriction via endothelium‐dependent or endothelium‐independent mechanisms and by genomic or non‐genomic modes of action (31).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…VEGF plays a critical role in ovarian folliculogenesis and normal reproductive function [8], highlighted by the findings that women with PCOS had increased serum levels of VEGF, which paralleled increases in Doppler flow velocities within ovarian vessels [10, 11]. High vascularization may result in abnormal growth of the theca interna, the site of androgen steroidogenesis, leading to hyperandrogenism, a hallmark of PCOS [12, 13]. VEGF is encoded by VEGFA gene, which is located on chromosome 6 (6p21.3), and comprises eight exons separated by seven introns [14].…”
Section: Introductionmentioning
confidence: 99%